Sebaran suhu dan Salinitas di Perairan Kayo Pulau, Kota Jayapura - Umbekna, Sara; Tuhumena, Lolita; Muhammad Hisyam; Huwae, Jilian Risky (Cenderawasih University, 2023)
Temperature and salinity are oceanographic parameters that play an important role in physical, chemical and biological process in the sea, such as in mixing process, dissolved oxygen concentration and the distribution of marine organisms. This study aims to determine the distribution of temperature and salinity in the waters of Kayo Pulau, Jayapura City. The study was conducted in November 2023. Temperature and salinity were measured using a digital thermometer and hand refractometer. Water samples were taken at a depth of 1 m at 5 observation stations spread around Kayo Pulau Village. The study found, the temperature in the waters of Kayo Pulau ranged from 29.2-29.5°C, with an average temperature of 29.3°C. The salinity in Kayo Island waters is very high, ranged from 33.40-35.00%0, with an average of 34.28%0. The temperature and salinity in Kayo Pulau waters are still within the optimal range to support the survived of marine organisms